Bug-fixing and code-writing : the private provision of open source software - Jürgen Bitzer; Philipp J. H. Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
Open source software (OSS) is a public good. A self-interested individual would consider providing such software, if the benefits he gained from having it justified the cost of programming. Nevertheless each agent is tempted to free ride and wait for others to develop the software instead. This problem is modelled as a war of attrition with complete information, job signaling, repeated contribution to the public good and uncertainty in programming. The resulting game does not feature any delay: software will be provided swiftly, by young, low-cost individuals who gain considerably by signaling their programming skills; the startup (and collapse) of an OSS project displays bandwagon dynamics.
Keywords: H41; L86; L31; 330; open source software; war of attrition; public goods; Open Source; Programmierung; Spieltheorie; Öffentliches Gut; Qualifikation; Signalling; Theorie; war of attrition